2010
DOI: 10.1371/journal.pone.0011972
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group and Incidence of Skin Cancer

Abstract: BackgroundPrevious studies have examined the association between ABO blood group and the risk of some malignancies. However, no prospective cohort study to date has examined the association between ABO blood group and the risk of skin cancer.Methodology/Principal FindingsUsing two large cohorts in the US, we examined ABO blood type and incidence of skin cancer, including melanoma, squamous cell carcinoma (SCC), and basal cell carcinoma (BCC). We followed up study participants (70,650 female nurses and 24,820 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 16 publications
1
93
2
Order By: Relevance
“…Similarly, Iodice et al demonstrated that most of the patients with non-melanoma skin cancer had A Rh positive (Iodice et al, 2010). In another study, Xie et al (2010) investigated the relationship between the blood groups and incidence of skin cancer in participants with 0 blood group and non-0 blood group. The authors reported that participants with non-0 blood group had a reduced risk by 14% for developing SCC and by 4% for developing BCC.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Iodice et al demonstrated that most of the patients with non-melanoma skin cancer had A Rh positive (Iodice et al, 2010). In another study, Xie et al (2010) investigated the relationship between the blood groups and incidence of skin cancer in participants with 0 blood group and non-0 blood group. The authors reported that participants with non-0 blood group had a reduced risk by 14% for developing SCC and by 4% for developing BCC.…”
Section: Discussionmentioning
confidence: 97%
“…Genetic studies have demonstrated that individuals with A blood group are more resistant to the influenza virus, despite a higher risk profile for acute rheumatism, whereas individuals with 0 blood group are highly resistant to the viruses despite a higher risk profile for gastric cancer, ulcer and other forms of cancer. In addition, although it has been reported that several forms of cancer are associated with subtypes of ABO blood groups, the exact mechanism of this association remains to be elucidated (Rolfe et al, 2002;Adamian, 2005;Hosoi, 2008;Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confounding factors were not included in our metaanalysis as the case in most of the studies included. Several studies performed multivariate analysis, while the results changed little compared with univariate analysis (Xie et al, 2010;Joh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that carriers of the blood group O had a 4% reduced risk of basal cell carcinoma and 14% reduced risk of squamous cell carcinoma within the large cohort of US individuals (Xie et al, 2010). Likewise, it has been demonstrated that subjects possessing the blood group O have a lower risk of pancreatic cancer compared to those with groups A or B (Amundadottir et al, 2009;Wolpin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%